2020
DOI: 10.3390/soc10020033
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to a Rights-Based Approach in Sexual Health Policy: A Comparative Study of Turkey and England

Abstract: Politics around sexual health have been polarised in recent years, but the policy implications of this polarisation have not yet been examined in depth. Therefore, this article explores political challenges to a rights-based approach in sexual health policies in Turkey and England. Its focus is on two domains: The prevention and treatment of sexually transmitted infections (STI), and sexual health education. Drawing on an interpretive documentary analysis, this article reveals that although social attitudes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…However, here we would like to acknowledge the influence of a contemporary political context in certain European countries that may compromise the autonomy of sexual health policy and promotion, which is another important impetus for highlighting research priorities on a transnational scale. For example, in Turkey, policy changes from the early 2010s demonstrate an evident distancing trend from individual rights-based sexual/reproductive health policy framework which dominated during the 2000s (Yilmaz & Willis, 2020). Similar broader conservative turn has also been observed in Hungary and Poland (Pugh, 2019), and recent reports reveal how their new legislative changes could harm HIV response and adequate sexual education, respectively (Davies, 2020;Holt, 2021).…”
Section: Care and Policy Aimed At Better Sexual Healthmentioning
confidence: 86%
“…However, here we would like to acknowledge the influence of a contemporary political context in certain European countries that may compromise the autonomy of sexual health policy and promotion, which is another important impetus for highlighting research priorities on a transnational scale. For example, in Turkey, policy changes from the early 2010s demonstrate an evident distancing trend from individual rights-based sexual/reproductive health policy framework which dominated during the 2000s (Yilmaz & Willis, 2020). Similar broader conservative turn has also been observed in Hungary and Poland (Pugh, 2019), and recent reports reveal how their new legislative changes could harm HIV response and adequate sexual education, respectively (Davies, 2020;Holt, 2021).…”
Section: Care and Policy Aimed At Better Sexual Healthmentioning
confidence: 86%
“…For example, the implementation of Health Transformation Program in Turkey in 2010 likely decreased the provision of family planning services (Öcek et al 2014;Ozaydin et al 2020) 6 . Researchers have also suggested that the broad conservative turn in Turkey has undermined the autonomy of sexual health policy by subjecting it to population policy (Yilmaz and Willis 2020), and "politics of the intimate" that overemphasizes motherhood and procreation (Acar and Altunok 2013) has likely impacted service delivery at the institutional level (MacFarlane et al 2016). Similarly, we should note the increased political polarization in France in the recent years, with far-right candidates employing anti-immigrant sentiments and calling for less state aid for migrants (AP 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These health centers provided modern contraceptives free of charge and played an important role in providing family planning services to vulnerable groups such as migrants and uninsured individuals (Öcek et al 2014). Nonetheless, concerns persist about gaps in the contraceptive knowledge (Yilmaz and Willis 2020) and access (Tatar et al 2011).…”
Section: Contraception In Turkeymentioning
confidence: 99%
“…For example, the implementation of the Health Transformation Program in Turkey in 2010 likely decreased the provision of family planning services (Öcek et al 2014; Ozaydin et al 2020). 12 Researchers have also suggested that the broad conservative turn in Turkey has undermined the autonomy of sexual health policy by subjecting it to population policy (Yilmaz and Willis 2020), and “politics of the intimate” that overemphasizes motherhood and procreation (Acar and Altunok 2013) has likely affected service delivery at the institutional level (MacFarlane et al 2016). Similarly, we should note the increased political polarization in France in the recent years, with far-right candidates using anti-immigrant sentiment and calling for less state aid for migrants (News Wires 2022).…”
Section: Discussionmentioning
confidence: 99%